In-Kind Government Assistance and Crowd-Out of Charitable Services: Evidence from Free School Meals - Krista Ruffini; Orgül Öztürk; Pelin Pekgün (Center for Economic Studies and ifo Institute (CESifo), 2023)
Many community organizations provide services similar to government programs, but there is limited evidence how increased government assistance affects the use of charitable services. We examine how greater access to federal nutritional aid through schoolwide free meal programs affects food bank use across the US's largest food bank network. We find that a 10% increase in free school meal access reduces food bank utilization by 0.9-1.4%, without significantly reducing the amount of charitable resources available. The reduction of food bank use is only found in areas where relatively few students qualified for government aid prior to universal meals.
Keywords: H53; I00; J38; 330; crowd-out; charitable donations; nutritional assistance; food banks